2013
DOI: 10.1128/jvi.02329-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Reveal Fundamental Structural and Functional Differences between the Two Progeny Phenotypes of a Baculovirus

Abstract: The replication of lepidopteran baculoviruses is characterized by the production of two progeny phenotypes: the occlusion-derived virus (ODV), which establishes infection in midgut cells, and the budded virus (BV), which disseminates infection to different tissues within a susceptible host. To understand the structural, and hence functional, differences between BV and ODV, we employed multiple proteomic methods to reveal the protein compositions and posttranslational modifications of the two phenotypes of Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 70 publications
8
103
0
7
Order By: Relevance
“…Previous research suggested that ME53 may provide a scaffold that bridges the viral envelope and nucleocapsid (de Jong et al, 2011). As a common protein amongst the baculovirus genomes, ME53 was identified on the BVs of AcMNPV and HearNPV (Hou et al, 2013;Wang et al, 2010), whilst in this and PrGV studies it was identified as an ODV protein.…”
Section: Proteins Present Only In Betabaculovirus Odvsmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous research suggested that ME53 may provide a scaffold that bridges the viral envelope and nucleocapsid (de Jong et al, 2011). As a common protein amongst the baculovirus genomes, ME53 was identified on the BVs of AcMNPV and HearNPV (Hou et al, 2013;Wang et al, 2010), whilst in this and PrGV studies it was identified as an ODV protein.…”
Section: Proteins Present Only In Betabaculovirus Odvsmentioning
confidence: 91%
“…1). They covered 59.3 % of the complete theoretical proteome of ClanGV, which was a much higher percentage than those of other baculoviruses whose ODV compositions were successfully analysed by MS approaches (HearNPV, 42.2 %; CuniNPV, 41.3 %; PrGV, 39.2 %; ChchNPV, 35.1 %; AgMNPV, 28.9 %; AcMNPV, 28.6 %) (Braconi et al, 2014;Braunagel et al, 2003;Hou et al, 2013;Perera et al, 2007;Wang et al, 2011;Xu et al, 2011).…”
Section: Comparison Of the Protein Compositions Of Baculovirus Odvsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that AcMNPV deleted for ac23, an ortholog of the F fusion protein gene of Group II viruses (see above), shows an elevated percentage of singly enveloped virions, 45 % vs 11-22 % for different virus constructs that contained ac23 [19]. Although characterized as a BV-associated protein in AcMNPV [20], OpMNPV [21], and HearNPV [22], Ac23 was reported to be associated with AcMNPV ODV [23], suggesting that it could be directly involved in formation of the MNPV morphotype. Also a knockout (KO) of ac43 appeared to increase the number of SNPVs in occlusion bodies, and co-infection of the ac43 KO virus with a virus encoding ac43 restored the predominance of the MNPV morphotype [24].…”
Section: Nucleocapsid Aggregation: Multiple Versus Single Nucleocapsimentioning
confidence: 99%